2021
DOI: 10.7759/cureus.14816
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic Turner Syndrome With 45,X/46,XY Mosaicism and Apparent Absent Uterus

Abstract: Turner syndrome (TS) is a relatively common chromosomal abnormality in females. Short stature, gonadal dysgenesis, and somatic dysmorphic features are the characteristic features of the syndrome. The chromosomal abnormalities of TS are highly variable; 45,X/46,XY mosaicism accounts for 10-12% of cases of Turner syndrome. Despite the presence of hypogonadism, affected females typically have a uterus. Here, we report the case of a 22-year-old female who presented at 15 years of age with primary amenorrhea. She w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Jie Xu et al found that > 20% of G-banded amniocytes with idic Yp seemed to correlate with phenotypically healthy males in most cases in the absence of other indicators of fetal structural anomalies [ 44 ]. High levels of the mosaicism of 45,X and low levels of idic(Y)/i(Y) cell lines in gonads may lead to mosaic loss, the haploinsufficiency of SRY , and an inability to maintain normal testosterone differentiation, thus manifesting in ambiguous genitalia or a female phenotype [ 45 48 ]. However, a lack of correlation between the level of mosaicism in AF cells and the phenotypic sex has been reported [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jie Xu et al found that > 20% of G-banded amniocytes with idic Yp seemed to correlate with phenotypically healthy males in most cases in the absence of other indicators of fetal structural anomalies [ 44 ]. High levels of the mosaicism of 45,X and low levels of idic(Y)/i(Y) cell lines in gonads may lead to mosaic loss, the haploinsufficiency of SRY , and an inability to maintain normal testosterone differentiation, thus manifesting in ambiguous genitalia or a female phenotype [ 45 48 ]. However, a lack of correlation between the level of mosaicism in AF cells and the phenotypic sex has been reported [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…As in the presented case, gonads are frequently a unilateral dysgenetic testis and a contralateral streak-like gonad with persistent asymmetrical Mullerian structures: underdeveloped uterus, fallopian tube ipsilateral to the streak-like gonad [ 6 , 13 ]. The broad range of phenotypical variations in MGD may be explained by the proportion of mosaic karyotype that is expressed in gonadal and other tissue cells [ 14 , 15 ]. Frequently Turner syndrome characteristics are found in individuals with 45,X/46,XY, the presence of 45,X cell line is associated with Turner syndrome fenotype [ 5 , 7 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The broad range of phenotypical variations in MGD may be explained by the proportion of mosaic karyotype that is expressed in gonadal and other tissue cells [ 14 , 15 ]. Frequently Turner syndrome characteristics are found in individuals with 45,X/46,XY, the presence of 45,X cell line is associated with Turner syndrome fenotype [ 5 , 7 , 15 , 16 ]. Gonadal development and differentiation is determined by the predominant karyotype in gonadal tissue cells.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Y chromosome material with a dysgenic gonad increases the risk of gonadoblastoma, which is further increased if the gonad is undescended. 38,39 The percentage of Y chromosome-containing cells on the peripheral blood karyotype may correlate with degree of virilization of the external genital structures, but this association is imperfect. Some features of TS are common in those with Y chromosome mosaicism, such as reduced growth, and gonadal dysfunction.…”
Section: X and Mosaic 45x-neurodevelopmental Considerationsmentioning
confidence: 99%
“…External genitalia may develop into typically female, typically male, or neither typically male nor female (intersex). The presence of Y chromosome material with a dysgenic gonad increases the risk of gonadoblastoma, which is further increased if the gonad is undescended 38,39 . The percentage of Y chromosome‐containing cells on the peripheral blood karyotype may correlate with degree of virilization of the external genital structures, but this association is imperfect.…”
Section: X and Mosaic 45xmentioning
confidence: 99%